(untitled) (Orfeu, 2021)
Barbara Nissman is a North-American pianist known for her recordings of Alberto Ginastera and Sergei Prokofiev. Ginastera´s Sonata n. 3, his last work, was dedicated to her. She was the first to record the complete cycle of Piano Sonatas by S. Prokofiev, in 1989. Alongside her performance activities, she authored the book Bartók and the piano: A performer´s view. Ms. Nissman is a frequent guest artist/clinician, regularly invited to performances, lectures, and masterclasses. Her undergraduate and graduate studies took place at the University of Michigan, under the tutelage of pianist Gyorgy Sandor, a pupil of Béla Bartók. She released an extensive discography and educational DVDs that combine lectures and performances.